Regenerative technologies to bed side: Evolving the regulatory framework - Daisuke Sakai; Jordy Schol; Casper B. Foldager; Masato Sato; Masahiko Watanabe (Journal of Orthopaedic Translation, 2017)
There are high expectations for the clinical application of regenerative medicine technologies to treat musculoskeletal disorders. However, there are still big hurdles in bringing cell-based products to the market, mainly due to strict regulatory frameworks to approve these. Recently, the Japanese Pharmaceuticals and Medical Devices Agency adopted new regulations under legislature. The translational potential of this article is to inform on the regulations to bring experimental phase regenerative concepts to market approval in the United States and Europe, and highlight the opportunities granted by Japanese regulatory framework. Furthermore, we discuss the perspectives on the quickly evolving regulatory environment.